2021
DOI: 10.1186/s12889-020-10060-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Active Kids voucher program on children and adolescents’ physical activity: a natural experiment evaluating a state-wide intervention

Abstract: Background There is an urgent need for scaled-up effective interventions which overcome barriers to health-enhancing physical activity for children and adolescents. In New South Wales (NSW), Australia, the state government implemented a universal voucher program, ‘Active Kids’ to support the cost of structured physical activity registration for school-enrolled children aged 4.5–18 years old. The objective of this study was to understand the effects a financial incentive intervention delivered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
(73 reference statements)
0
28
0
Order By: Relevance
“…Sport has several additional costs such as registration, uniform, travel, and equipment, which can present greater barriers for children and adolescents from disadvantaged backgrounds. This cost barrier to sport has been addressed through financial incentive programs across the world [ 50 ] which have shown some promising findings (e.g., [ 51 ]). However, there are socioeconomic disparities in awareness and engagement in these programs and further targeted work is needed [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sport has several additional costs such as registration, uniform, travel, and equipment, which can present greater barriers for children and adolescents from disadvantaged backgrounds. This cost barrier to sport has been addressed through financial incentive programs across the world [ 50 ] which have shown some promising findings (e.g., [ 51 ]). However, there are socioeconomic disparities in awareness and engagement in these programs and further targeted work is needed [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community acceptance has proven greater for interventions representing the status quo 18,19 and we found greater support for existing interventions compared to speculative ones, illustrated through consistently higher support for food environment policies for schools, 33 hospitals and health facilities, 34 and for information campaigns 35 and children's sports rebates 36 . This may reflect a preference to target children or other vulnerable groups 18,20 or enhanced perceptions of government responsibility within institutions that have historical engagement in health‐promoting activities and are typically responsible for leading by example.…”
Section: Discussionmentioning
confidence: 66%
“…However, such options only further widen socioeconomic disparities with barriers such as cost, accessibility, and lack of local facilities affecting families from the most disadvantaged backgrounds [ 76 , 77 ], something that was also identified by the parents in this research. A recent analysis has also shown that SES is inversely linked with sports expenditure, with an AUD 311 difference in median expenditure between the most and least disadvantaged populations [ 78 ]. However, the implementation of the Active Kids Voucher program in NSW is a clear demonstration of the power of upstream policies and programs to support physical activity participation.…”
Section: Discussionmentioning
confidence: 99%